Corruption at the grassroots : the shades and shadows - Narayanasamy, N.; Boraian, M. P.; Jeyaraju, M. A.; National Workshop on "Corruption at the Grassroots" (1998 : Madras, India) (New Delhi : Concept Pub., 2000)
Papers presented at the National Workshop on "Corruption at the Grassroots" held at Chennai on Dec. 3, 1998
Includes bibliographical references and index
Keywords: Political corruption -- India -- Congresses; Business enterprises -- Corrupt practices -- india; Bribery -- India